Stabilization of black cotton soil by using cement, lime and rice husk in flexible pavements - Satish, Sajja; Prakash Koganti, Shyam; Hemantha Raja, Kommineni; Raaga Sai, Kaza (International Journal of Engineering and Technology, 2018)
Expansive soil (Black cotton soil) is very weak and does not have enough stability for any type of construction work. To make the subgrade soil stable, by improving its engineering properties is very essential. In the present work, stabilization of subgrade soil by using Sand and Cement varying percentage of cement as 2%, 3%, 5% and constant percentage of sand by weight of soil, Rice Husk of 5%, 7%, 10%, and Lime is used to enhance the strength of subgrade soil. The purpose of this study is to determine the optimum dose of the stabilizer, which improves the strength and bearing capacity of soil less which is suitable for pavement structure. To evaluate the strength of soil, various tests have been performed such as Sieve analysis, Liquid limit, Plastic limit, Specific gravity, Compaction (OMC, MDD) and CBR test in the laboratory. The result shows that the use of the above materials in combination increases the California Bearing Ratio values (CBR). By using the CBR value the design of pavements to carry traffic in the range of 1 to 10 msa and 10 – 150 msa is calculated as per IRC: 37 – 2001.